Late Ediacaran juvenile magmatism in the Variscan Monts-du-Lyonnais metamorphic complex (Massif Central, France) - Couzinié Simon; Laurent Oscar; Bouilhol Pierre; Chelle-Michou Cyril; Ganzhorn Anne-Céline; Gardien Véronique; Moyen Jean-François (BSGF - Earth Sciences Bulletin)
The identification of oceanic sutures is key to understanding the evolution of the Paleozoic Variscan belt and the structure of the West European lithosphere. In the French Massif Central, the suture of the ‘Mid-Variscan’ ocean would be stamped by distinctive lithological formations known as ’Leptynite–Amphibolite Complexes’ (LACs). These formations comprise various Cambrian–Ordovician (meta-)igneous associations, commonly interpreted as representing rifted-margin magmatism, and experienced Devonian (385–360 Ma) high-pressure metamorphism. Our study provides geochronological and geochemical data on mafic–felsic rocks from the Riverie LAC in the Monts-du-Lyonnais metamorphic complex. In the Riverie LAC, metaluminous, amphibole-bearing felsic gneisses represent former tonalites closely associated with mafic rocks (now amphibolites). LA–ICP–MS zircon U–Pb dating reveals a latest Ediacaran (c. 545 Ma) crystallization age for the melt that yielded the tonalites. Whole-rock geochemistry (notably pronounced Nb negative anomalies) and the highly radiogenic zircon Hf isotope compositions, with εHf(545Ma) of c. +11 (within the range expected for the Depleted Mantle reservoir), indicate that the parental melt of the tonalites ultimately originated from a mantle source metasomatized by oceanic slab-derived fluids. The (meta-)mafic rocks share a similar ’arc’ signature and were possibly generated from the same mantle source. The mafic–felsic association of the Riverie LAC is unrelated to the opening and closure of the Mid-Variscan ocean and does not represent its suture. Instead, it can be correlated to a juvenile Ediacaran magmatic event identified throughout the Variscan realm, interpreted as reflecting Cadomian arc/back-arc magmatism.